NEW RECORD OF HALIMEDACEAN ALGAE FROM THE UPPER TRIASSIC OF THE SOUTHERN ALPS (DOLOMITES, ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
A new record of halimedacean algae is reported from the Upper Triassic (Carnian) of the Dolomites (Southern Alps) near Cortina d’Ampezzo. Based on the gross morphology (non-segmented non-branched thalli) and the internal skeletal arrangement (e.g., medulla with thicker siphons, sometimes bifurcating at high angles; cortex with thinner siphons with multiple Y-like branching), the material can be assigned to the genus Boueina. It is the first record of halimedacean algae from the Upper Triassic of the Southern Alps (Dolomites) and the highly diverse San Cassiano Formation sensu lato (Heiligkreuz Formation). Although the fossilization potential of these algae was low, it is likely that they were much more common than suggested by this sparse fossil record and that they contributed considerably to carbonate production in early Mesozoic times.